Coordinated public policies and coalition presidentialism: the case of PROMESO - Rocha Neto, João Mendes da (2016)
Public policies have been studied with various theoretical aspects as a basis. However, there is still a gap on issues related to the interconnection of actions taken by government agencies. These dimensions, when addressed, do not get close to the perspective of impacts derived from the architecture of coalition presidentialism on public policies, which, in the Brazilian case, corroborates its fragmentation and competition between government agencies that should work in an interconnected way. This article aims at identifying where this problem is expressed and the inflection point between the discourse of coordinated action and an implementation showing the opposite. To demonstrate how this occurs, we chose the Brazilian Program for Promoting Sustainability in Sub-Regional Spaces (PROMESO), which has shared agendas as one of its significant instruments. Research construction required a theoretical review that focuses on the institutional architecture of coalition presidentialism and political parties, besides adopting, in empirical investigation, the database of the Brazilian Federal Budget Department (SOF/MPOG) and the Brazilian Interconnected System of Government Financial Administration (SIAFI/MF), which enabled us to spatialize the distribution of public resources according to a party and region-based rationale, and refer to official documents from the Brazilian Ministry of National Integration (MI) that characterize the program addressed in this study. The research proved that coalition presidentialism directly affects public policies, highlighting a competitive nature between the federal government agencies, due to particular rationales, determined by directors at these institutions.